Role of Lung Ultrasound in Determining the Endpoint of Fluid Therapy in Patients With Septic Shock - Salah Eldeen Mohammed, Walaa; Gouda, Tarek Elsayed; Abdel Hafez, Afaf; Elmansy, Mostafa; Abd El-Hamid Mousa, Samar (Scripta Medica, 2026)
Background/Aim: Fluid resuscitation in septic shock is essential, but determining the optimal volume remains challenging. This research aimed to evaluate the role of lung ultrasound (LUS) in assessment of endpoint of fluid therapy in septic shock. Methods: This prospective observational research comprised 60 adults with septic shock admitted to critical care unit between May 2024 and December 2025. Fluid responsiveness was assessed by left ventricular outflow tract velocity–time integral (LVOT VTI) variation during passive leg raise; ≥ 10 % increase defined responders. LUS was performed using simplified, quantitative eight zone and qualitative eight zone protocols. Echocardiographic evaluation of left ventricular systolic and diastolic function, along with inferior vena cava collapsibility index (IVCCI), was also performed. Results: Thirty-five patients (58.3 %) were fluid responders and 25 (41.7 %) non-responders. Non-responders exhibited lower IVCCI and higher prevalence of diastolic dysfunction, particularly grades II–III. The simplified LUS score (cut-off ≥ 11) showed excellent discrimination of fluid unresponsiveness [AUC 0.913 (95 % CI 0.844 – 0.983)]. The quantitative 8-zone score (cut-off ≥ 4) had good performance [AUC 0.834 (95 % CI 0.732 – 0.942)], while the qualitative protocol had the highest specificity for discriminating fluid unresponsiveness (sensitivity 76 %, specificity 85.5 %). Combining LUS with echocardiography improved identification of patients unlikely to benefit from further fluid. Conclusion: LUS, particularly the simplified protocol, may serve as a bedside tool to predict fluid unresponsiveness and guide resuscitation endpoints in septic shock. Combined with echocardiography, it supports a multimodal, individualised approach that minimises overload risk.